Evaluation of Adhesion and Co-culture Efficacy Assays of Antifungals and Chlorhexidine Against Acanthamoeba and Candida Species Associated with Severe Infectious Keratitis - Dayara Corrêa Matiola; Gabriella da Rosa Monte Machado; Gabrieli Eduarda Israel; Alexandre Meneghello Fuentefria; Karin Silva Caumo (Current Microbiology, 2026)

Optimization of corneal preservation media with novel antifungal agents - Paula Reginatto; Giovanna de Jesus Agostinetto; Claudete Inês Locatelli; Felipe Silva Guareze; Angélica Rocha Joaquim; Maria Eduarda Krummenauer; Rúbia do Nascimento Fuentefria; Marilene Henning Vainstein; Diane Ruschel Marinho; Saulo Fernandes de Andrade; Alexandre Meneghello Fuentefria (Archives of Microbiology, 2026)
The performance of ophthalmic surgeries, particularly penetrating keratoplasty, is associated with an increased risk of ocular infections, especially fungal keratitis. In addition to infections such as post-surgical occlusions, microbial contamination of the donor’s tissue, predominantly fungal in nature, can also lead to the disposal of said tissue. The genus Fusarium , along with several species from the Candida genus, emerge as the primary fungal agents, displaying notable biofilm-forming abilities on surfaces. To address these issues, the addition of antifungals to preservation media vials has been explored, although conventional antifungal agents exhibit limitations. In light of this, compounds such derived from 8-hydroxyquinoline, clioquinol (CLQ) and PH151, emerge as promising alternatives. Hence, this study aimed to assess the efficacy of two derivatives of 8-hydroxyquinoline, both individually and in combination with antifungal agents, as additives in preservation media for human corneas intended for transplantation. Given the antifungal potential of CLQ and the combination voriconazole-amphotericin B-clioquinol, the ability to inhibit fungal growth and biofilm formation in human corneas preserved in Optisol-GS medium was investigated, as well as the endothelial viability of this tissue in the presence of these compounds. Among the tested antifungal agents, the combination of voriconazole, amphotericin B, and clioquinol stood out for its excellent antibiofilm action and potential to reduce the fungal load on the surface of the corneas, did not present endothelial toxicity. Thus, the results underscore the promising nature of this combination as a potential additive in hypothermic corneal preservation media, outlining a viable pathway to enhance corneal transplant efficacy.

Polymeric Nanocapsules Containing Ozonated Oil and Terbinafine Hydrochloride as a Potential Treatment Against Dermatophytes - Francielli Lima dos Santos; Júlia Capp Zilles; Andressa Urbano Machado; Morgana Souza Marques; Bárbara Souza da Costa; Irene Clemes Kulkamp Guerreiro; Alexandre Meneghello Fuentefria; Renata Vidor Contri (AAPS PharmSciTech, 2023)

Eye fungal infections: a mini review - Paula Reginatto; Giovanna de Jesus Agostinetto; Rubia do Nascimento Fuentefria; Diane Ruschel Marinho; Melissa Dal Pizzol; Alexandre Meneghello Fuentefria (Archives of Microbiology, 2023)

Are γ-terpinene, 1,8-cineole, p-coumaric acid, and quercetin active against wild-type and non–wild-type Sporothrix brasiliensis to itraconazole? - Stefanie Bressan Waller; Márcia Kutscher Ripoll; Helena Piúma Gonçalves; Daiane Flores Dalla Lana; Renata Osório de Faria; Mário Carlos Araújo Meireles; Alexandre Meneghello Fuentefria; João Roberto Braga de Mello; Marlete Brum Cleff (Brazilian Journal of Microbiology, 2023)

A chloroacetamide derivative as a potent candidate for fusariosis treatment - Gabriella da Rosa Monte Machado; Stefânia Neiva Lavorato; William Lopes; Marilene Henning Vainstein; Mário Lettieri Teixeira; Ricardo José Alves; Saulo Fernandes de Andrade; Alexandre Meneghello Fuentefria (Brazilian Journal of Microbiology, 2022)

Antimicrobial activity of clioquinol and nitroxoline: a scoping review - Rachel Wykowski; Alexandre Meneghello Fuentefria; Saulo Fernandes de Andrade (Archives of Microbiology, 2022)

Fungicide Resistance in Fusarium graminearum Species Complex - Magda Antunes de Chaves; Paula Reginatto; Bárbara Souza da Costa; Ricardo Itiki de Paschoal; Mário Lettieri Teixeira; Alexandre Meneghello Fuentefria (Current Microbiology, 2022)

In vivo protection of the marjoram ( Origanum majorana Linn.) essential oil in the cutaneous sporotrichosis by Sporothrix brasiliensis - Stefanie Bressan Waller; Marlete Brum Cleff; Caroline Bohnen de Mattos; Cristine Cioato da Silva; Cláudia Giordani; Daiane Flores Dalla Lana; Alexandre Meneghello Fuentefria; Rogério Antônio Freitag; Eliza Simone Viegas Sallis; João Roberto Braga de Mello; Renata Osório de Faria; Mário Carlos Araújo Meireles (Natural Product Research, 2021)

Glass ionomer cement modified by a imidazolium salt: adding antifungal properties to a biomaterial - Alexandre Ehrhardt; Jéssica Zolim Andreatto Mandelli; Vanessa Bérgamo; William Lopes; Ricardo Keitel Donato; Régis A. Zanette; Alexandre Meneghello Fuentefria (Brazilian Journal of Microbiology, 2021)

Occurrence and impact of fungicides residues on fermentation during wine production– A review - Angelo Gava; Cassandro Davi Emer; Evandro Ficagna; Saulo Fernandes de Andrade; Alexandre Meneghello Fuentefria (Food Additives & Contaminants: Part A, 2021)

Antifungal resistance on Sporothrix species: an overview - Stefanie Bressan Waller; Daiane Flores Dalla Lana; Priscilla Maciel Quatrin; Marcos Roberto Alves Ferreira; Alexandre Meneghello Fuentefria; Adelina Mezzari (Brazilian Journal of Microbiology, 2021)

Quinolines derivatives as promising new antifungal candidates for the treatment of candidiasis and dermatophytosis - Gabriella da Rosa Monte Machado; Denise Diedrich; Thaís Carine Ruaro; Aline Rigon Zimmer; Mário Lettieri Teixeira; Luís Flávio de Oliveira; Mickael Jean; Pierre Van de Weghe; Saulo Fernandes de Andrade; Simone Cristina Baggio Gnoatto; Alexandre Meneghello Fuentefria (Brazilian Journal of Microbiology, 2020)

Rational selection of antifungal drugs to propose a new formulation strategy to control Candida biofilm formation on venous catheters - Paula Reginatto; Vanessa Zafanelli Bergamo; Simone Jacobus Berlitz; Irene Clemes Kulkamp Guerreiro; Saulo Fernandes de Andrade; Alexandre Meneghello Fuentefria (Brazilian Journal of Microbiology, 2020)

Epidemiological Profile of Cryptococcal Meningitis Patients in Rio Grande do Sul, Brazil - Ana Lusia Leal; Josiane Faganello; Alexandre Meneghello Fuentefria; Juliano Tomazzoni Boldo; Maria Cristina Bassanesi; Marilene H. Vainstein (Mycopathologia, 2008)